(untitled) (International Journal of Food and Nutritional Sciences, 2023)
A well-known Indian writer and social activist Arundhati Roy is the author of award-winning novel The God of Small Things. She is not only a writer but a political figure who is fighting for injustice done to the human beings all over the world. Her famous book God of Small Things describes the dark face of the Indian society where women and marginalised victimised by the power of men. She also uncovers the ill-treatments done to the women by the patriarchy. Roy exposes issues of gender discrimination, caste and class conflicts, color and racial distinction. She raises the question on human rights. She describes minutely how the women and the down trodden are victimised in the hands of male dominated society and powerful. The research throws the light on the typical society where discrimination and injustice are in their regular mode of practice in their daily life.